PENGARUH TEKNOLOGI INFORMASI, CITRA PERUSAHAAN, DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA BANK SUMSEL BABEL SYARIAH CABANG PEMBANTU SUNGAILIAT - Siti Napisah (JEM Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study was to see the effect of Technology Information, Corporate Image, and Customer Satisfaction on Customer Loyalty of Bank Sumsel Babel Syariah Sungailiat Branch. The sampling technique used in this study is non-probability sampling, namely a sampling technique that does not provide equal opportunities or opportunities for each element or member of the population to be selected as a sample, distributing questionnaires to Islamic savings customers and filling in answers using a Likert scale, where in the data analysis using an instrument test to measure the validity of each answer item and measure the level of reliability of each variable, followed by using the classical assumption test, regression analysis and hypothesis testing. In the regression analysis, it is obtained that the regression line is Y = 3,363 + 0,366 + 0,248 + 0,211 + e, which shows a positive value meaning that the three X variables affect variable Y. Based on simultaneous and partial hypothesis testing, there are results that information technology, corporate image, and Customer satisfaction has a positive and significant effect, and the information technology variable is the variable with the most dominant influence, namely 0.366 with a significant value of 0.000 <0.05.